PENGEMBANGAN E-LKPD BERBASIS GUIDED INQUIRY PADA MATERI SISTEM EKSKRESI MANUSIA - Sofiah, Sofiah; Fikriyah, Aida; Tamam, Badrud; Rendy Astid Putra, Dwi Bagus; Sutarja, Maria Candra (Program Studi Pendidikan IPA, Universitas Trunojoyo Madura, 2023)
The Guided Inquiry-based digital student worksheet is a learning media resulting from innovation from technological developments, with the intention of making science learning material on the human excretory system more interesting and easier for students. The development design used is ADDIE (Analyze, Design, Developemet, Develop, Implementation, and Evaluation). This study aims to determine the feasibility of learning media, readability, and student responses to digital student worksheet media. The trial was conducted on 20 students of class VIII A at SMP Al-Hamidiyah. The results of the study show that: (1) digital student worksheet media is suitable for use as learning media with an average validity result on media aspects of 88 in the very valid category. The average result of the validity of the material aspect is 75 in the valid category. (2) The average readability result is 87% in the very interesting category, indicating that the guided inquiry-based digital student worksheet has very interesting readability, and (3) The average student response result is 74% in the interesting category indicating that students are very interested in reading guided inquiry-based digital student worksheet.